Alternative healthcare delivery arrangements in Nepal: a systematic review of comparative effectiveness, safety and cost-effectiveness studies - Rachelle Buchbinder; Shyam Sundar Budhathoki; Denise A O’Connor; Ilana Ackerman; Pramila Rai (BMJ Global Health)
Background The way that healthcare services are organised and delivered (termed ‘healthcare delivery arrangements’) is a key aspect of a health system. Changing the way health care is delivered, for example, task shifting that delivers the same care at lower cost, may be one way of improving healthcare system sustainability. We synthesised the existing randomised trial evidence to compare the effects of alternative healthcare delivery arrangements versus usual care in Nepal.Methods For eligible studies published since 2005, we searched MEDLINE, Embase, CENTRAL, CINAHL, Scopus, the WHO clinical trials registry and NepJOL on 31 October 2024. Two authors independently assessed studies for eligibility, extracted data and evaluated the risk of bias using the Cochrane risk of bias tool and certainty of evidence using Grading of Recommendations, Assessment, Development and Evaluations. We calculated risk ratios (RRs), mean differences (MDs) and percentage points (PPs) with 95% CIs for the outcomes and performed meta-analysis where appropriate.Results Four studies met the inclusion criteria. One evaluated task shifting, two information and communication technology, and one care coordination. No meta-analyses were performed. Low certainty evidence indicates task shifting of medical abortion by doctors to midlevel providers may result in equivalent complete abortion (RR: 2.55, 95% CI: 0.82 to 4.27). Similarly, the use of a mobile phone call reminder may improve on-time medicine collection among patients with HIV compared with usual care (RR: 1.29, 95% CI: 1.12 to 1.48), while the integration of postpartum family planning and postpartum intrauterine contraceptive device (PPIUCD) insertion with maternity services may improve PPIUCD uptake compared with usual care (PP: 0.173, 95% CI: 0.098 to 0.246).Conclusion More evaluation is needed for alternative delivery arrangements due to limited low-certainty evidence from current trials. There was insufficient evidence on outcomes such as cost, safety, and patient and provider perspectives.PROSPERO registration number CRD42022327298.